Reduced-scale hot box method for thermal characterization of window insulation materials. (September 2019) - Zhao, Xinpeng; Mofid, Sohrab A.; Al Hulayel, Majed R.; Saxe, Gabriel W.; Jelle, Bjørn Petter; Yang, Ronggui
Highlights: A reduced-scale hot box is built to measure window insulation materials. The built system can measure the specimens with sizes < 0.2 m × 0.2 m accurately. The thermal conductivity and U-value of transparent porous aerogel are measured. Abstract: Highly transparent and low thermal conductivity materials have attracted great interest for the applications in window insulation in recent years. Accurate characterization of the thermal properties including thermal transmittance (U-value) and thermal conductivity of window insulation materials is very important for developing next-generation materials. The conventional hot box method, which is commonly used to measure the U-values of building materials, requires sample sizes > 1.0 m 2 to minimize the influence of parasitic heat loss on the measurement accuracy. This characterization challenge hinders the development of novel window materials which are not yet available for large-scale deployment. To address this issue, a reduced-scale hot box system (RHS) was designed to measure both the U-value and the thermal conductivity of specimens that can be more readily made, with sizes < 0.2 m × 0.2 m. The developed reduced-scale hot box system has a very simple testing system and can avoid the challenging thermal insulation requirement of the conventional hot box. The fast turnaround of the reduced-scale hot box system can help facilitate the development of novel insulating materials for energy-efficient windows.